PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM DI SEKOLAH DASAR - Hati, Dinda Permata; Sabri, Tahmid; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The problem in this study is "How the Problem Based Learning Model Influences Science Learning Outcomes of Class III Students in State Elementary Schools 01 Sui Raya". This study aims to describe the influence of the use of problem based learning models in learning scienceclass III State Elementary School 01 Sui Raya. This research uses the Experimental Method of Pre-Experimental Design with the Nonequivalent Control Group Design. The population in this study were all students of class III State Elementary School 01 Sui Raya. The sample in this study were all students of class III A, amounting to 29 students as a control class, and students of class III B, amounting to 29 students as an Experiment class. Data collection techniques used are direct observation techniques, and measurements. Data collection tools used were observation sheets and multiple choice tests. Based on the results of data analysis, the average control class pre-test was 57.78 and the post-test control class was 73.57. The average pre-test of the experimental class was 57.36 and the post-test of the experimental class was 79.52. From the results of the calculation of the Effect Size (ES) is equal to 0.42 including medium classification. This shows that the problem based learning model has a moderate effect on learning outcomes in learning Natural Sciences in class III State Elementary School 01 Sui Raya.Key words : Influence, Problem Based Learning Model, Learning Outcomes, NaturalSciences.